Empirical Validation of the Genetic Psychosocial Risk Instrument – French Version (GPRI-F) - Maheu, Christine; Esplen, Mary Jane; Gao, Xin; Dzneladze, Irakli; Bai, Hao; Eisinger, François; Julian-Reynier, Claire (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2018)
Objective. This study sought to validate a French version of the Genetic Psychosocial Risk Instrument (GPRI), an instrument used to screen for psychosocial risk in individuals undergoing genetic testing for adult-onset hereditary disease (AOHD). Methods. The French translation of the GPRI (GPRI-F) was first validated linguistically with ten French individuals undergoing genetic testing for AOHD. Then, a psychometric evaluation of the GPRI-F was carried out with a separate cohort of 132 individuals. Convergent validity was assessed with the Impact of Event Scale (IES) and the Perceived Risk Scale (PR), while divergent validity was assessed with a quality of life measure, the SF-8. Results. The 20-item GPRI-F obtained a Cronbach’s α of .81, indicating a good level of internal consistency. Factor analysis yielded a psychometrically sound four-factor solution. The optimal GPRI-F cut-off was determined to be 55 and resulted in an area under the curve of .769. The GPRI-F also had improved sensitivity and specificity relative to the onco-genetic assessment of the treating medical doctor. The GPRI-F was also found to have satisfactory internal validity. Discussion and conclusions. Overall, the psychometric properties obtained in this study support the reliability and validity of using the GPRI-F with French-speaking individuals scheduled to receive genetic counselling and testing to identify those who are at heightened psychological risk and who might benefit from added psychosocial support.